Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am learning about a Bell State, and am trying to show that they are entangled. I believe that the required proof is to show that the system

$$\alpha_0^2+\alpha_1^2=1$$ $$\beta_0^2+\beta_1^2=1$$ $$\alpha_0\beta_0=1/\sqrt{2}$$ $$\alpha_1\beta_1=1/\sqrt{2}$$

has no solutions. I have tried various ways of rewriting each variable in terms of others etc. without success. Any hints?

EDIT: I apologize, I should have made clear. In QM probabilities can be complex - what exactly this means intuitively is unclear to me, but algebraically it means that $\alpha_i,\beta_i$ can be complex.

share|cite|improve this question
The equations have complex solutions. What are the restrictions on the solutions in this context? Not everyone here is familiar with Quantum Mechanics. – Ayman Hourieh Jun 16 '12 at 16:38
@Ayman: My apologies, I have updated the question. AFAIK, the only remarkable thing about this system that I didn't mention is that there can be complex solutions. – Xodarap Jun 16 '12 at 18:35
up vote 2 down vote accepted

From (3) and (4), we have: \begin{align*} \beta_0^2 &= \frac{1}{2\alpha_0^2} \\ \beta_1^2 &= \frac{1}{2\alpha_1^2} \end{align*}

Plug into (2): \begin{align*} \frac{1}{2\alpha_0^2} + \frac{1}{2\alpha_1^2} &= 1 \\ \frac{\alpha_1^2}{\alpha_0^2\alpha_1^2} + \frac{\alpha_0^2}{\alpha_0^2\alpha_1^2} &= 2 \\ \frac{\alpha_0^2 + \alpha_1^2}{\alpha_0^2\alpha_1^2} &= 2 \end{align*}

Use (1) in the numerator to get: $$ \alpha_0^2 \alpha_1^2 = \frac{1}{2} $$

Therefore: $$ \alpha_1^2 = \frac{1}{2\alpha_0^2} $$

Plug into (1) and multiply both sides by $\alpha_0^2$: $$ \alpha_0^4 - \alpha_0^2 + \frac{1}{2} = 0 $$

This is a quadratic equation for $\alpha_0^2$ with no real solutions, as $\Delta = -1 \lt 0$.

share|cite|improve this answer
I believe amplitudes can be complex so showing non-real solutions doesn't satisfy, unfortunately. – Xodarap Jun 16 '12 at 15:20
But complex solutions are still solutions depending on the context, aren't they? – Bolutife Ogunsola Jun 16 '12 at 15:27
@Xodarap - I'm not familiar with this topic in Quantum Mechanics and thought that the values were supposed to be real. Of course, the equations have complex solutions and they all satisfy $|\alpha|^2 \le 1$. Are there other restrictions on the values? – Ayman Hourieh Jun 16 '12 at 16:32
You're right, there are complex solutions. My problem is probably at the physics level, not the math level, so I will ask there. – Xodarap Jun 16 '12 at 18:41

By the first equation we may write $$ \alpha_0 = \sin(x), \alpha_1=\cos(x)$$ and by the second $$\beta_0 = \sin(y), \beta_1 = \cos(y).$$ Multiplying the third and fourth equations then gives $$(\sin(x)\cos(x))(\sin(y)\cos(y)) = \left(\frac{1}{2}\sin(2x)\right)\left(\frac{1}{2}\sin(2y)\right) = \frac{1}{2} $$ $$\iff \sin(2x)\sin(2y) = 2 $$ which is not possible since the product of two numbers with absolute value at most 1 has absolute value at most 1.

share|cite|improve this answer

$${1\over 2}(\alpha_0-\beta_0)^2 + {1\over 2}(\alpha_1 - \beta_1)^2 = {1\over 2}(\alpha_0^2 + \beta_0^2 + \alpha_1^2 + \beta_1^2) - \alpha_0\beta_0 - \alpha_1\beta_1 = 1 - {2\over \sqrt{2}} = 1 - \sqrt{2}.$$

Since the left-hand side is a sum of squres, you are now done.

share|cite|improve this answer
Nice solution!${}{}{}{}{}$ – André Nicolas Jun 16 '12 at 15:11
Sorry, could you expand? If it is a sum of squares then...? The amplitudes can be complex – Xodarap Jun 16 '12 at 15:21
You did not specify this is a complex system. – ncmathsadist Jun 16 '12 at 17:21

Another trigonometric approach: let $x$ and $y$ be such that $\alpha_0 = \sin x$ and $\beta_0 = \sin y$, as in nullUser's answer.

Then use the following identities on the third and fourth equations: $$\sin s \sin t = \frac{\cos (s-t) - \cos (s+t)}{2}$$ $$\cos s \cos t = \frac{\cos (s-t) + \cos (s+t)}{2}$$

This gives the following system of equations: $$\cos (s-t) - \cos (s+t) = \sqrt{2}$$ $$\cos (s-t) + \cos (s+t) = \sqrt{2}$$ From this it is clear that $\cos (s-t) = \sqrt{2}$, but that is impossible.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.